Gamma Interferon Is Required for Chlamydia Clearance but Is Dispensable for T Cell Homing to the Genital Tract - Helble, Jennifer D. (mBio, 2020)
While there is no effective vaccine against Chlamydia trachomatis infection, previous work has demonstrated the importance of C. trachomatis-specific CD4(+) T cells (NR1 T cells) in pathogen clearance. Specifically, NR1 T cells have been shown to be protective in mice, and this protection depends on the host’s ability to sense the cytokine gamma interferon (IFN-γ). However, it is unclear what role NR1 production or sensing of IFN-γ plays in T cell homing to the genital tract or T cell-mediated protection against C. trachomatis. Using two-photon microscopy and flow cytometry, we found that naive wild-type (WT), IFN-γ(−/−), and IFN-γR(−/−) NR1 T cells specifically home to sections in the genital tract that contain C. trachomatis. We also determined that protection against infection requires production of IFN-γ from either NR1 T cells or endogenous cells, further highlighting the importance of IFN-γ in clearing C. trachomatis infection.